2004
DOI: 10.1191/1352458504ms1071oa
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of caspase-1 and interleukin-18 in peripheral blood mononuclear cells in patients with multiple sclerosis

Abstract: Multiple sclerosis (MS) is supposedly a T-cell mediated autoimmune disorder of the central nervous system. Cytokines and other molecules involved in the regulation of apoptosis are thought to be of importance for the pathogenesis of MS. In this study, the mRNA levels of interleukin 18 (IL-18), IL-1beta and their processing enzyme caspase-1 were quantified by a competitive RT-PCR method in unstimulated peripheral blood mononuclear cells (PBMCs) in MS patients never treated with disease modifying drugs. Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 33 publications
3
75
0
1
Order By: Relevance
“…In contrast, expression of HLA-DR class II molecule was up-regulated in CD11c high NK cells. Notably, both CD11c and HLA-DR on NK cells were reproducibly induced in vitro in the presence of IL-15 (11) or combination of inflammatory cytokines, known to be increased in the blood of MS (12)(13)(14). Furthermore, we found that the remission state of CD11c high is unstable in comparison to CD11c low , as judged by an increased number of the patients who exacerbated during the 120 days after examining NK cell phenotypes.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 77%
“…In contrast, expression of HLA-DR class II molecule was up-regulated in CD11c high NK cells. Notably, both CD11c and HLA-DR on NK cells were reproducibly induced in vitro in the presence of IL-15 (11) or combination of inflammatory cytokines, known to be increased in the blood of MS (12)(13)(14). Furthermore, we found that the remission state of CD11c high is unstable in comparison to CD11c low , as judged by an increased number of the patients who exacerbated during the 120 days after examining NK cell phenotypes.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 77%
“…Caspase-1 has been implicated in both human and mouse neuroinflammation. Caspase-1 levels are significantly increased in peripheral blood mononuclear cells from MS patients (Huang et al, 2004). Moreover, caspase-1 is known to contribute to the pathology of EAE (Furlan et al, 1999;Ahmed et al, 2002).…”
Section: Il-1␤mentioning
confidence: 99%
“…We and another group reported that mice lacking genes for Nlrp3 or Asc (Nlrp3 −/− and Asc −/− mice) are resistant to the development of EAE (6,7), suggesting the association of the NLRP3 inflammasome with EAE development. In MS plaques and/or cells from MS patients, the expression of caspase-1, IL-1β, and IL-18 is elevated (8)(9)(10), suggesting the involvement of the NLRP3 inflammasome in MS pathogenicity. However, the mechanism by which the NLRP3 inflammasome induces development of EAE and MS is poorly understood.…”
mentioning
confidence: 99%